2020
DOI: 10.1128/msphere.00828-19
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus 16 E6 and E7 Synergistically Repress Innate Immune Gene Transcription

Abstract: Human papillomaviruses (HPV) are causative agents in 5% of all cancers, including the majority of anogenital and oropharyngeal cancers. Downregulation of innate immune genes (IIGs) by HPV to promote the viral life cycle is well documented; E6 and E7 are known repressors of these genes. More recently, we demonstrated that E2 could also repress IIGs. These studies have been carried out in cells overexpressing the viral proteins, and to further investigate the role of individual viral proteins in this repression,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Indeed, IFN responses are detrimental to persistent HPV infections, reducing cellular proliferation and causing apoptosis, episome loss, mutation, and/or integration [73][74][75][76][77]. Likewise, it is well known that some HPV early genes-E5, E6, and E7 -counteract these detrimental antiviral IFN and IFN-stimulated gene (ISG) responses through a variety of mechanisms [78][79][80][81].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, IFN responses are detrimental to persistent HPV infections, reducing cellular proliferation and causing apoptosis, episome loss, mutation, and/or integration [73][74][75][76][77]. Likewise, it is well known that some HPV early genes-E5, E6, and E7 -counteract these detrimental antiviral IFN and IFN-stimulated gene (ISG) responses through a variety of mechanisms [78][79][80][81].…”
Section: Introductionmentioning
confidence: 99%
“…This results in the decreased expression of ISGs, such as IFIT1, MX1 and OAS1. Furthermore, the authors demonstrated that IFNβ treatment of HPV16 containing N/Tert1s restores expression of the ISGF3 complex, but not ISG expression, suggesting that HPV16 can also regulate ISG expression independently of the ISGF3 complex [128]. In this study, the viral genes E2, E6 and E7 were responsible for the downregulation of the ISGF3 complex and downstream ISG expression.…”
Section: Interaction Of Hpv With Stat1/2 Signallingmentioning
confidence: 55%
“…Importantly, they also showed that IFNβ treatment activated STAT1 in HPV-containing keratinocytes and reduced genome amplification, suggesting that downregulation of STAT1 is an essential, conserved function of HR-HPV E6 and E7 during the viral life cycle. Additionally, the persistence of HPV16 viral genomes also resulted in the suppression of ISGs, IFNs and STAT1 [127,128].…”
Section: Interaction Of Hpv With Stat1/2 Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses that encode anti-apoptotic protease are likely to inhibit the apoptosis process to facilities its replication and spreading 26 . Several similar viruses encode Bcl-2 homologs, which inhibit activation of apoptotic caspases and block the death of the host cell 27 as well as interfering with other proapoptotic molecules, for example papillomavirus E7 and HHV-8 that encodes several versions of the IRFs, which interferes with normal IRF function 28 . Many viruses take advantage of apoptosis to facilitate its replication 27; the major protein involved in the apoptosis process is a family of cysteine-dependent aspartate-directed proteinases called caspases 29 .…”
Section: Apoptosis Between Immunity and Sars-cov-2 Infection Strategiesmentioning
confidence: 99%